The study of the correlations between handgrip strength and some anthropometric characteristics of upper extremity of elite and subelite olympic style weightlifting athletes - Erdagi, K. (Physical Education of Students, 2020)
Purpose: Handgrip strength is widely used as a functionality parameter of the upper extremity and general health. The measurement of handgrip strength by dynamometry is a low cost, noninvasive method of simple applicability. The study aims to find out handgrip strength and its correlation with some anthropometric characteristics of the upper extremity and weightlifting performance of elite (international medalists) and sub-elite (national medalists) Olympic style weightlifting athletes. Material: We obtained anthropometric measurements of upper extremity of elite athletes (n=25 male, n= 20 female) and sub-elite athletes (n=25 male, n=29 female) in the study. Dominant and non-dominant handgrip strength measurements of the groups were obtained by a Jamar dynamometer, according to the recommendations of the American Association of Hand Therapists. Results: No statistically significant difference was observed in non-dominant handgrip strength of male elite and subelite weightlifting athletes. Similarly, no significant difference was observed in between some anthropometric characteristics of upper extremity and dominant and non-dominant handgrip strength of female elite and sub-elite weightlifting athletes. We didn`t find any asymmetry between dominant and non-dominant handgrip strength of study groups. We found a significant correlation between dominant and non-dominant handgrip strength of male and female elite athletes and their height, body weight, BMI and weightlifting performance. Conclusions: Consequently, we might explain that adding special exercises into the general trainings of athletes to develop handgrip strength might contribute to the weightlifting performance of the athletes. Keywords: olympic-style weightlifting, elite athletes, handgrip strength, anthropometry.